Antiproliferative activity of isolated compounds from Pinus dalatensis and Pinus krempfii on acute myeloid Leukemia cells. Issue 4 (23rd August 2019) - Sa, Nguyen Hoang; Tam, Nguyen Thanh; Quan, Tran Duc; Anh, Nguyen Thi Hoang; Linh, Nguyen Thi Thuy; Nhung, Le Thi Hong; Adorisio, Sabrina; Delfino, Domenico V; Van Sung, Tran; Thuy, Trinh Thi
Abstract: Our previous chemical constituent study of Pinus dalatensis and Pinus krempfii had identified six compounds 1‐6 . The continuing investigation of biological activity of the conifer species led to discovery of the antiproliferative activity of all isolated compounds 1‐6 on acute myeloid leukemia cells as shown by the effects on cell cycle progression. Remarkably, compound 3 (chrysin) exibited potent bioactivity at the concentration of 10 μg/mL.